Measuring the effects of liquid bulk viscosity numerically on a spherical nitrogen bubble in aqueous H2SO4 - P. K. Mall; H. K. Paliwal; Amit Medhavi; Ayman A. Aly (AIP Advances)
The current study extensively simulates multiple theories concerning the mechanism of bubble formation during the interaction between an aqueous H2SO4 solution and nitrogen gas. This interaction leads to pressure surges and high internal temperatures due to the violent collapse of the inertial bubble. This study examines the effects of liquid volume viscosity on the dynamics of a single cavitation bubble by applying the Gilmore model to the bubble interface under various boundary conditions, such as liquid volume, N2, surface tension, temperature, pressure, etc. An aqueous solution of H2SO4 in liquid and nitrogen bubbles was used in this investigation. A comprehensive study of the effects of bubble frequency, asymptotic growth, and viscosity on bubble growth was carried out. To quantitatively investigate the influence of fluid shear viscosity on the dynamics of a single cavitation bubble, several numerical calculations were performed at various viscosities ranging from 0.002 to 0.014 Pa s, both with and without fluid shear viscosity. In addition, the study focuses on the maximum stress in the bubble rather than the highest temperature. Wherever possible, the experimental validations that serve as a guide for the theoretical predictions are also provided. The findings indicate that while the impact on a bubble boom may be negligible at lower viscosities, it cannot be completely ignored at relatively high viscosities. This analysis offers insight into how the thermodynamic method modifies the intensity of cavitation and advances our understanding of this complex thermal-hydrodynamic phenomenon.